Study the effect of Chemical and Organic fertilizers on some physiological, phonological and yield traits of Peanut (Damascus University Journal of agriculture sciences, 2022)
The experiment was carried out during the growing season 2020 to find out the effect of chemical fertilizers and organic bioslurry fertilizer on some physiological, phenological and productive traits of peanut, at Zahed Station for Water and Irrigation Research, which is located in Tartous Governorate - Syria. The experiment was designed according to Randomized Complete Blocks Design (RCBD), with three replicates.The results of the statistical analysis for the BS treatments showed the superiority of the third level (T4) treatment (10) L / m2 over the first and second level (T2) and (T3) treatments in total number of leaves, leaf area index, wet weight, dry weight and protein ratio (251.33 leaf. plant-1, 1.72, 371.89 g, 131.16 g, 24.69 %) respectively, while the treatments of BS (T3) and (T4) showed no significant difference regarding sees yield (2.06 and 2.17 ton. ha-1) respectively.The results showed that for CF and BS treatments, CF (T1) and BS of third level (T4) (10) L / m2 had the same effect on all studies traits. Also, it was showed the superiority of both CF and BS over fertilizer, control treatment (without fertilizer) for all studies traits.
Keywords: Arachis hepogaya; Peanut; Growth Parameters Traits; Yield; Chemical Fertilizer; Bioslurry Fertilizer